Delayed versus immediate oxytocin infusion after amniotomy for induction of labour: A randomised controlled pilot trial. (September 2019) - Titulaer, Linde M.L.; de Wolf, G. Sander; Bakkum, Erica A.; Moll, Etelka
Abstract: Objective: To get a preliminary understanding of the amniotomy-to-delivery interval, patients' experiences and risks by awaiting spontaneous contractions after amniotomy and to explore the need and feasibility for a larger randomised controlled trial. Methods: We performed a randomised controlled pilot trial in a peripheral teaching hospital in Amsterdam, The Netherlands. Women with term, singleton pregnancy in vertex position undergoing labour induction for one of the five following indications: prolonged pregnancy, mild hypertensive disorders, diabetes, expected macrosomia, maternal request, were randomised to amniotomy with 12-hours delayed oxytocin (DO), or amniotomy with immediate oxytocin (IO). Results: A total of 64 women was included in the analysis. The median amniotomy-to-delivery interval for the DO-group was 15 h (IQR 8–21), and 6 h (IQR 5–11) for the IO-group (HR, 0.41; 95% CI, 0.24–0.70), with equal patient reported childbirth perception in the overall group ( P =0.43). Parous women reported a significantly less positive perception of labour ( P =0.02) and used pain relief more often (RR, 2.93; 95% CI, 1.05–8.19) in the DO-group. The proportion of women delivered within 24 h was not significantly different between groups (RR, 0.30; 95% CI, 0.05–1.83). Other delivery and neonatal outcomes did not differ significantly between groups, possibly due to being underpowered. Conclusion: Preliminary results show that amniotomy-to-delivery interval was prolonged with 9 h in the DO-group, with equal patient reported childbirth perception in the overall group. Parous women have a less positive perception of their delivery and used pain relief more often when oxytocin was delayed. Delaying oxytocin infusion after amniotomy should be further investigated in an adequately powered randomised trial.